2012
DOI: 10.1371/journal.pone.0051382
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting Mental Simulation in Language Comprehension: Six Replication Attempts

Abstract: The notion of language comprehension as mental simulation has become popular in cognitive science. We revisit some of the original empirical evidence for this. Specifically, we attempted to replicate the findings from earlier studies that examined the mental simulation of object orientation, shape, and color, respectively, in sentence-picture verification. For each of these sets of findings, we conducted two web-based replication attempts using Amazon's Mechanical Turk. Our results are mixed. Participants resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

17
180
6
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 173 publications
(205 citation statements)
references
References 41 publications
17
180
6
2
Order By: Relevance
“…Though falsifying data was rated as neither prevalent nor defensible, a few practices were prevalent (e.g., failing to report all dependent measures, reporting only studies that confirmed the hypothesis, data peeking), and many were viewed as defensible (John, Loewenstein, & Prelec, 2012 Kerr (1998) reports that in an unpublished study, over half of his respondents said that editors had asked them to alter a hypothesis post hoc. OPEN SCIENCE 8 Pashler, 2013;Johnson, Cheung, & Donnellan, 2014;LeBel & Campbell, 2013;Lynott et al, 2014;McDonald, Donnellan, Lang, & Nikolajuk, 2014;Pashler, Coburn, & Harris, 2012;Shanks et al, 2013;Zwaan & Pecher, 2012 widely shared e-mail that with regards to that research area: "I see a train wreck looming" (Kahneman, 2012).…”
Section: Major Motivations For Concernmentioning
confidence: 99%
See 1 more Smart Citation
“…Though falsifying data was rated as neither prevalent nor defensible, a few practices were prevalent (e.g., failing to report all dependent measures, reporting only studies that confirmed the hypothesis, data peeking), and many were viewed as defensible (John, Loewenstein, & Prelec, 2012 Kerr (1998) reports that in an unpublished study, over half of his respondents said that editors had asked them to alter a hypothesis post hoc. OPEN SCIENCE 8 Pashler, 2013;Johnson, Cheung, & Donnellan, 2014;LeBel & Campbell, 2013;Lynott et al, 2014;McDonald, Donnellan, Lang, & Nikolajuk, 2014;Pashler, Coburn, & Harris, 2012;Shanks et al, 2013;Zwaan & Pecher, 2012 widely shared e-mail that with regards to that research area: "I see a train wreck looming" (Kahneman, 2012).…”
Section: Major Motivations For Concernmentioning
confidence: 99%
“…At the same time that psychologists were acknowledging the prevalence of QRPs, researchers across the field had become more vocal about being unable to replicate others' findings, including some that were well-cited and ground-breaking (Donnellan, Lucas, & Cesario, 2015;Doyen, Klein, Pichon, & Cleeremans, 2012;Harris, Coburn, Rohrer, & Pashler, 2013;Johnson, Cheung, & Donnellan, 2014;LeBel & Campbell, 2013;Lynott et al, 2014;McDonald, Donnellan, Lang, & Nikolajuk, 2014;Pashler, Coburn, & Harris, 2012;Shanks et al, 2013;Zwaan & Pecher, 2012). Although there have always been failures to replicate, now many of them were occurring in multiple laboratories and, because of new media, there was increasing recognition that the failures were not isolated to single labs or lines of research.…”
Section: --Table 1 -Insert Timeline Of Current Events About Here --mentioning
confidence: 99%
“…We put a sample of these findings to a particularly stringent test by running them under circumstances that are increasingly representative of current practices of data collection but also are documented as challenging for reproducibility. In particular, we conducted the first preregistered replication of a large set of cognitive psychological effects in the most popular online participant pool (Crump, McDonnell, &Gureckis, 2013 andPecher, 2012 for non-preregistered replications on MTurk). Most importantly, we examined whether reproducibility depends on participant nonnaïveté by conducting the same experiments twice on the same participants a few days apart.…”
mentioning
confidence: 99%
“…We think this opposition is visible in psycholinguistics, too. Conceptual and direct replication research is unfortunately very sparse (but see Nieuwland et al, 2017;Rommers, Meyer, & Huettig, 2013;Zwaan & Pecher, 2012; see also Jäger, Engelmann, & Vasishth, 2017), and even novel but incremental contributions are often considered insufficient for publication.…”
Section: Resultsmentioning
confidence: 99%